Why am I here, and what is here anyway? : a social constructionist window into clinical psychology : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Adam, Dean (Massey University, 2001)
Understandings of why people enter into careers as clinical psychologists are underdeveloped. This thesis uses a social construction perspective to explore the question of how clinical psychology students explain their career choice, and in particular how expectations and understandings of a career in clinical psychology are constructed as influencing such a decision. Interview transcripts from six clinical psychology students were analysed using a combined methodology of Heideggerian hermeneutics and discourse analysis of a thematic nature. The themes developed outline how the participants constructed clinical psychology, the process of choosing such a career, related professions, what it meant to 'be' a clinical psychologist, and other peoples' perceptions of clinical psychology. The conclusion of these findings suggest the need for multidisciplinary awareness in the training of clinical psychologists, the need for an increased focus on long term career satisfaction and goal achievement, and attention to the education of the public about the role and utility of clinical psychology.
Keywords: Clinical psychology; Clinical psychologists